KONSTRUKSI KONSTITUSI KEADILAN SOSIAL DI INDONESIA BERBASIS NILAI-NILAI ISLAM - Rewapatara, Hendrik Rikarsyo; Sofian, Muhamad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
To strive for increasing social welfare can be started by Building the idea of a Social Justice Constitution based on the values of Islamic teachings. This research aims to examine the normative basis of social justice in the Indonesian constitution, Identify relevant Islamic values in social justice and Offer the construction of Islamic-based social justice in a constitutional context. The type of research used is Normative legal research using a statute approach and Literature Review (library research). The results of the study show that constitutionally, social justice in Indonesia is a fundamental principle in state life. The principle of social justice for all Indonesian people is the philosophical foundation for the state to realize social justice. Islam makes social justice an effort to eliminate both economic and social disparities and ensure that everyone has equal standing and treatment as well as access to all that is the right of citizens. The construction of a social justice constitution can be attempted first, through the Integration of Social Justice in all branches of state power; second, constitutional provisions with affirmative action guarantees for vulnerable groups; third, management of natural resources and state wealth for the greatest possible prosperity of the people; Fourth, the state is responsible for basic services for a dignified life; Fifth, a monitoring mechanism in the implementation of social justice policies in all sectors; Sixth, the integration of local wisdom and/or religious values in social justice policies. The construction of a social justice constitution, when viewed from an Islamic perspective, will be in line with the principles of Al-’Adl (justice) and Al-Maslahah (public benefit). In addition, social justice can be in line with the objectives of Islamic law to protect religion, protect the soul, protect the mind, protect descendants, and protect property.